Intensity of Physical Activity and Its Impact on Sleep Pattern in Sport Players - Saini , Preeti; Sharma, Mahak; Sethi, Priyanka (Current Overview on Disease and Health Vol. 7, 2023)
The purpose of this study was to look at the relationship between physical activity and sleep among sports players. The current study was conducted in Faridabad with a sample size of 133 sports participants aged 18 to 25. Runners, shooters, and archers were the subjects. According to the study findings, all of the runners (100%) were engaging in intense activity. 72.7% of archers engaged in moderate activity, while 58.8% of shooters engaged in sedentary activity. The majority of sports participants had a fairly high quality of sleep (P=0.65). Around 30% of sports players engaged in moderate activity had poor sleep latency, while 17.5% engaged in vigorous activity had poor sleep length, however the differences were not statistically significant when compared to other groups (P=0.303; P=0.32 respectively). All of the sports players had good Habitual Sleep efficiency, and the majority of them slept well without interruptions. No one on the team was taking sleep medication. There was no link found between the subjects' Global Physical Activity Questionnaire Score and any Sleep Domain. The study concluded that different sports players who engaged in sedentary, moderate, or heavy physical activity were getting sufficient sleep. This means that even a small amount of physical activity can help you sleep better.